Da’i Muda Pilihan (DMP) ANTV dalam Perspektif Dakwah - Fatmawati Fatmawati (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2012)
This paper attempts to unravel the involvement of media in orbit would be preachers and da'iah as a television program. The position of television as a medium to be very important in clarifying the boundaries of da'iah professionalism because a preacher or items related to the assessment standards applied by the media as an organizer of the contest. In addition, this paper also presents the phenomenon of young preachers that the selection program is a form of positive cooperation between the Islamic syi'ar the media so that the message of Islam can exist in the development of information and communication technology is rapidly increasing.